The Impact Of Tourism Feature Writing On Branding Strategy Sustainable Tourism Destinations - Ronny Sugiantoro (Sean Institute, 2024)
Mass media are tools and facilities that have an important role in disseminating information to readers, so the media must be able to present the message or news that readers want. This research aims to determine the pattern of writing tourism features in Indonesia using a social cognition and social context analysis approach in digital media tourism news KRJOGJA.com and Republika.co.id. The method used in the research collaborates a qualitative research approach with Van Djik's critical discourse analysis method which consists of social cognition and social analysis, and adopts Zong Dang Pan and Gerald M. Kosicki's framing for aspects of the devices and units observed. The results of the research show that the pattern of writing Indonesian tourism features uses promotive, informative, provocative, persuasive sentences and refers to places and regional potential, always has an important event related to tourism as a background and shows details of things that stand out, uses interesting images and is in accordance with the theme of the discourse. . Using social cognition analysis, tourism feature writers include their own experiences regarding the culture they believe in to describe tourist destinations. By analyzing the social context, tourism feature writing adapts to the language use of readers who are members of the information society.